Cell-free translation and purification of Arabidopsis thaliana Regulator of G Signaling 1 protein - Li, Bo (Protein Expr Purif, 2016)
Arabidopsis thaliana Regulator of G protein Signalling 1 (AtRGS1) is a protein with a predicted N-terminal 7-transmembrane (7TM) domain and a C-terminal cytosolic RGS1 box domain. The RGS1 box domain exerts GTPase activation (GAP) activity on Gα (AtGPA1), a component of heterotrimeric G protein signaling in plants. AtRGS1 may perceive an exogenous agonist to regulate the steady-state levels of the active form of AtGPA1. It is uncertain if the full length RGS1 protein exerts any atypical effects on Gα, nor has it been established exactly how AtRGS1 contributes to perception of an extracellular signal and transmits this response to a G-protein dependent signaling cascade. Such an understanding can be deduced from in vitro studies using the purified and soluble RGS1-box domain. Further studies on full-length AtRGS1 have been inhibited due to the extreme low abundance of the endogenous AtRGS1 protein in plants and lack of a suitable heterologous system to express AtRGS1. Here, we describe methods to produce full-length AtRGS1 by cell free synthesis into unilamellar liposomes and nanodiscs. The cell-free synthesized AtRGS1 exhibits GTPase activating activity on Gα and can be purified to a level suitable for biochemical analyses.